Cardiopulmonary Capacity in Children During Exercise Testing: The Differences Between Treadmill and Upright and Supine Cycle Ergometry - Forbregd, Tonje Reitan; Aloyseus, Michelle Arthy; Berg, Ansgar; Greve, Gottfried (Frontiers in Physiology, 2019)
Background/Hypothesis: Cardiopulmonary exercise testing (CPET) is used in the assessment of function and prognosis of cardiopulmonary health in children with cardiac and pulmonary diseases. Techniques, such as cardiac MRi, and PET-scan, can be performed simultaneously with exercise testing. Thus, it is desirable to have a broader knowledge about children’s normal cardiopulmonary function in different body postures and exercise modalities. The aim of this study was to investigate the effect of different body positions on cardiopulmonary function in healthy subjects performing CPETs. Materials and Methods: Thirty-one healthy children aged 9, 12, and 15 years did four CPETs: one treadmill test with a modified Bruce protocol and three different bicycle tests with different body postures, sitting, tilted 45°, and lying flat (0°). For the bicycle tests, a 20-watt ramp protocol with a pedal frequency of 60 ± 5 rotations per minute was used. Continous ECG and breath-by-breath V.O2 measurements was done throughout the tests. Cardiac structure and function including aortic diameter were evaluated by transthoracic echocardiography prior to the tests. Doppler measurements of the blood velocity in the ascending aorta were measured prior to and during the test. Prior to every test, the participants performed pulmonary function tests with maximum voluntary ventilation test. Results: There is a significantly (p < 0.05) lower peak V.O2 in all bicycle tests compared with the treadmill test. There is lower corrected peak V.O2 (ml kg−0.67 min−1), but not relative peak V.O2 (ml kg−1 min−1), in the supine compared with the upright bicycle test. There are no differences in peak stroke volume or cardiac output between the bicycle modalities when calculated from aortic blood flow. Peak heart rate decreases from both treadmill to upright bicycle and from upright bicycle to the supine test (0°). Conclusion: There are no differences in peak cardiac output between the upright bicycle test and supine bicycle tests. Heart rate and corrected peak V.O2 are lower in the supine test (0°) than the upright bicycle test. In the treadmill test, it is a higher absolute and relative peak V.O2. Despite the latter differences, we are convinced that both upright and supine bicycle tests are apt in the clinical setting when needed.